2010
DOI: 10.1212/wnl.0b013e3181d9ed09
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive effects of treatment interruption in stable HIV-positive patients in an observational cohort

Abstract: Objective: Prior studies have shown improved neurocognition with initiation of antiretroviral treatment (ART) in HIV. We hypothesized that stopping ART would be associated with poorer neurocognitive function. Methods:Neurocognitive function was assessed as part of ACTG 5170, a multicenter, prospective observational study of HIV-infected subjects who elected to discontinue ART. Eligible subjects had CD4 count Ͼ350 cells/mm 3 , had HIV RNA viral load Ͻ55,000 cp/mL, and were on ART (Ն2 drugs) for Ն6 months. Subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
139
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(147 citation statements)
references
References 32 publications
6
139
1
1
Order By: Relevance
“…[30,31] Clinical studies have also suggested potential ART neurotoxicity. For example, Robertson et al [14] showed significant improvement in cognitive function in a cohort of patients taken off ART. There are many possible reasons for the conflicting literature regarding cognitive changes on higher CPE regimens.…”
Section: Follow-up Assessments N=121mentioning
confidence: 99%
See 1 more Smart Citation
“…[30,31] Clinical studies have also suggested potential ART neurotoxicity. For example, Robertson et al [14] showed significant improvement in cognitive function in a cohort of patients taken off ART. There are many possible reasons for the conflicting literature regarding cognitive changes on higher CPE regimens.…”
Section: Follow-up Assessments N=121mentioning
confidence: 99%
“…However, it may also relate to incomplete control of the virus and its effects on the CNS, and possibly to neurotoxicity of the antiretrovirals themselves. [14] One of the proposed reasons for the continually high incidence of HAND in the ART era relates to the difficulty posed by the bloodbrain barrier (BBB) for the passage of drugs into the CNS. Although previously investigated by many groups, a CNS penetration effectiveness (CPE) ranking system was formally proposed by Letendre et al [15] in 2008 and updated in 2010.…”
mentioning
confidence: 99%
“…In addition, highly active antiretroviral therapy (HAART) appears to have a positive impact on the WM in the temporal lobe 15 but with some toxicity. 16 The effects of HAART in adolescents are also uncertain; this uncertainty may be attributed to high rates of nonadherence 17 and loss to follow-up. 18 Therefore, in this study, we used DTI combined with TractBased Spatial Statistics (TBSS; http://fsl.fmrib.ox.ac.uk/fsl /fslwiki/TBSS) analysis to investigate the integrity of WM microstructure in adolescents with vertically transmitted HIV infections undergoing current HAART.…”
mentioning
confidence: 99%
“…Chronic administration of efavirenz, nevirapine or lopinavir/ ritonavir resulted in neuro behavioral impairment in mice [39,40]. Interestingly, a recent study by Robertson et al reported that discontinuation of cART was associated with the improvement in neurocognitive performance [41]. The same group also found that median toxic concentration of abacavir, didanosine, etravirine and nevirapine in rat cortical neurons was similar in range to CSF concentrations [42].…”
Section: Editorialmentioning
confidence: 99%